Seroprevalence and Distribution of Contagious Bovine Pleuropneumonia in Ethiopia: Update and Critical Analysis of 20 Years (1996–2016) Reports - Abdela, Nejash; Yune, Nesradin (Frontiers in Veterinary Science, 2017)
Contagious bovine pleuropneumonia (CBPP), infectious and highly contagious diseases of cattle in Africa, is the only bacterial disease in the OIE list A diseases. This severe respiratory disease of cattle is the second most important transboundary animal disease in Africa after rinderpest. CBPP is caused by Mycoplasma mycoides subsp. mycoides SC (small colony bovine biotype) and it is endemic disease in many African countries including Ethiopia. This paper systematically reviews prevalence report at herd and individual animal level for the last 20 years (1996–2016) with main aim of making comprehensive document regarding the seroprevalence and distribution of CBPP in Ethiopia. The paper is therefore helpful in knowing the past and current disease status and also to forecast the future and possible prevention option in the country. So far, the seroprevalence that ranges from 0.4 to 96% was reported from different export quarantine centers and production areas in Ethiopia. The reported seroprevalence is significantly associated with different agro-ecology of the country and the highest was reported from lowland in which 40% of livestock population was kept. The recent seroprevalence studies report from different areas of the country also indicated as CBPP is posing a major threat to cattle production in many parts of the country, thereby causing considerable economic losses through morbidity and mortality. This disease also causes restriction on the trade of animals and animal products internationally and accounts for a loss of over 8.96 million US dollars per year in Ethiopian situation. Thus, a great attention should be given both at production areas and the quarantine stations as its occurrence may affect the export earnings of the country, thereby threatening the livelihood of pastoralists and national economy of the country.